2,566 reputation
1619
bio website
location Yuseong-gu, Daejeon, Korea
age 35
visits member for 2 years, 1 month
seen 1 hour ago

I am studying Algebra.


1d
accepted Injectivity of Inflation Homomorphism $H^1(G/K,A^K)\rightarrow H^1(G,A)$
1d
revised Injectivity of Inflation Homomorphism $H^1(G/K,A^K)\rightarrow H^1(G,A)$
deleted 60 characters in body; edited title
1d
revised Injectivity of Inflation Homomorphism $H^1(G/K,A^K)\rightarrow H^1(G,A)$
edited body; edited title
1d
asked Injectivity of Inflation Homomorphism $H^1(G/K,A^K)\rightarrow H^1(G,A)$
2d
asked $ A\rightarrow M^G_H(A)$ induces ${\rm Res} : H^n(G,A)\rightarrow H^n(H,A)$
Sep
9
awarded  Popular Question
Sep
8
accepted Proof of $0\rightarrow A^G\stackrel{f}\rightarrow B^G\stackrel{h}\rightarrow C^G\rightarrow 0$
Sep
8
comment Proof of $0\rightarrow A^G\stackrel{f}\rightarrow B^G\stackrel{h}\rightarrow C^G\rightarrow 0$
Thank you. I see. And I check the statement on the book
Sep
8
asked Proof of $0\rightarrow A^G\stackrel{f}\rightarrow B^G\stackrel{h}\rightarrow C^G\rightarrow 0$
Sep
4
accepted Proof of the theorem: Any $R$-module is contained in an $R$-injective module
Sep
1
asked Proof of ${\rm Tor}\ (A,B)={\rm Tor}\ (B,A)$
Aug
30
comment Proof of the theorem: Any $R$-module is contained in an $R$-injective module
Yes, it is right
Aug
30
revised Proof of the theorem: Any $R$-module is contained in an $R$-injective module
added 103 characters in body
Aug
30
asked Proof of the theorem: Any $R$-module is contained in an $R$-injective module
Aug
26
accepted $\Delta e^i =0$ where $e_i$ is geodesic.
Aug
25
asked $\Delta e^i =0$ where $e_i$ is geodesic.
Aug
15
comment $A\otimes_RB$ is an $R$-algebra
I see. ${\mathbb Q}/{\mathbb Z}$ has no ring structure.
Aug
15
accepted $A\otimes_RB$ is an $R$-algebra
Aug
15
comment $A\otimes_RB$ is an $R$-algebra
In ${\mathbb Q}/{\mathbb Z}\otimes_{\mathbb Z} {\mathbb Z}$, $$ 0 = (1/3\otimes 3)(1/3\otimes 1)=1/3\otimes 1 $$
Aug
15
comment $A\otimes_RB$ is an $R$-algebra
You mean : $A\times B$ is $R$-algebra since $r(a,b)=(f(r)a,g(r)b)$